Climate therapy and the development of South Africa as a health resort, c.1850–1910 - Rogerson Christian M.; Rogerson Jayne M. (Bulletin of Geography. Socio-Economic Series)
Historical research is undeveloped concerning tourism in sub-Saharan Africa. This research contributes to scholarship about the history of tourism for climate and health. In South Africa the beginnings of international tourism are associated with its emergence as a health resort and to climate therapy. Using archival sources an analysis is undertaken of the factors that influenced the emergence of South Africa as a health destination during the 19th century. Climate therapy was of particular interest for the treatment of consumption or tuberculosis. Arguably, the perceived therapeutic regenerative qualities of South Africa's climate became a driver for the development of a form of international tourism that pre-dated the country's emergence as a leisure tourism destination.